Identification of Six New World Leishmania species through the implementation of a High-Resolution Melting (HRM) genotyping assay (2014)
Background: Leishmaniases are tropical zoonotic diseases, caused by parasites from the genus Leishmania. New World (NW) species are related to sylvatic cycles although urbanization processes have been reported in some South American Countries such as Colombia. This eco-epidemiological complexity imposes a challenge to the detection of circulating parasite species, not only related to human cases but also infecting vectors and reservoirs. Currently, no harmonized methods have been deployed to discriminate the NW Leishmania species. Findings: Herein, we conducted a systematic and mechanistic High-Resolution Melting (HRM) assay targeted to HSP70 and ITS1. Specific primers were designed that coupled with a HRM analyses permitted to discriminate six NW Leishmania species. In order to validate the herein described algorithm, we included 35 natural isolates obtained from human cases, insect vectors and mammals. Our genotyping assay allowed the correct assignment of the six NW Leishmania species (L. mexicana, L. infantum (chagasi), L. amazonensis, L. panamensis, L. guyanensis and L. braziliensis) based on reference strains. When the algorithm was applied to a set of well-characterized strains by means of PCR-RFLP, MLEE and monoclonal antibodies (MA) we observed a tailored concordance between the HRM and PCR-RFLP/MLEE/MA (KI = 1.0). Additionally, we tested the limit of detection for the HRM method showing that this is able to detect at least 10 equivalent-parasites per mL. Conclusions: This is a rapid and reliable method to conduct molecular epidemiology and host-parasite association studies in endemic areas. © 2014 Baleela et al.